Cost-Effectiveness of Adjuvant Immunotherapy With Cytokine-Induced Killer Cell for Hepatocellular Carcinoma Based on a Randomized Controlled Trial and Real-World Data - Cho, Jeong-Yeon; Kwon, Sun-Hong; Lee, Eui-Kyung; Lee, Jeong-Hoon; Kim, Hye-Lin (Frontiers in Oncology, 2021)
Background Studies using data from randomized controlled trials (RCTs) and real-world data (RWD) have suggested that adjuvant cytokine-induced killer (CIK) cell immunotherapy after curative treatment for hepatocellular carcinoma (HCC) prolongs recurrence-free survival (RFS) and overall survival (OS). However, the cost-effectiveness of CIK cell immunotherapy as an adjuvant therapy for HCC compared to no adjuvant therapy is uncertain. Methods We constructed a partitioned survival model to compare the expected costs, life-year (LY), and quality-adjusted life-year (QALY) of a hypothetical population of 10,000 patients between CIK cell immunotherapy and no adjuvant therapy groups. Patients with HCC aged 55 years who underwent a potentially curative treatment were simulated with the model over a 20-year time horizon, from a healthcare system perspective. To model the effectiveness, we used OS and RFS data from RCTs and RWD. We estimated the incremental cost-effectiveness ratios (ICERs) and performed extensive sensitivity analyses. Results Based on the RCT data, the CIK cell immunotherapy incrementally incurred a cost of 61,813, 2.07 LYs, and 1.87 QALYs per patient compared to no adjuvant therapy, and the estimated ICER was 33,077/QALY. Being less than the willingness-to-pay threshold of 50,000/QALY, CIK cell immunotherapy was cost-effective. Using the RWD, the ICER was estimated as 25,107/QALY, which is lower than that obtained using RCT. The time horizon and cost of productivity loss were the most influential factors on the ICER. Conclusion We showed that receiving adjuvant CIK cell immunotherapy was more cost-effective than no adjuvant therapy in patients with HCC who underwent a potentially curative treatment, attributed to prolonged survival, reduced recurrence of HCC, and better prognosis of recurrence. Receiving CIK cell immunotherapy may be more cost-effective in real-world clinical practice.